High-strength environment-friendly antibacterial cover plate glass as well as preparation method and application thereof
By introducing oxides of specific composition proportions into the cover glass and precisely controlling its content, combined with an optimized preparation process, the problem that existing cover glasses are difficult to take into account high strength, high transmittance and antibacterial properties, and the preparation of high-strength, excellent transmittance and environmentally friendly antibacterial cover glass is achieved.
Patent Information
- Application Number
- CN202411362810.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-05-02
AI Technical Summary
Existing cover glasses are difficult to take into account high strength, high transmittance and antibacterial properties, and are prone to heavy metal pollution and environmental pollution during the preparation process.
By introducing SiO2, Al2O3, B2O3, K2O, Na2O, CaO, MgO, CeO2, Bi2O3, Ag2O and In2O3 in a specific composition ratio into the glass, high-strength environmentally friendly and antibacterial cover glass is prepared in combination with precise control of the content of each component and the preparation process.
The high strength, excellent optical transmittance, good antibacterial properties and environmental protection of cover glass are achieved, reducing the risks of heavy metal pollution and environmental pollution.
Smart Images

Figure CN119912158A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to special glass materials, and in particular to a high-strength environmentally friendly antibacterial cover glass and a preparation method and application thereof. Background Art
[0002] At present, the mainstream cover material on the market is glass. Cover glass (Cover Lens or CoverGlass), also known as window protection screen, is mainly used in the front screen, back cover and other positions. Its basic functions are anti-fall, anti-scratch, anti-pressure, high temperature resistance, LCD protection, decoration, etc.
[0003] Since the cover glass requires high strength and scratch resistance, it is often necessary to introduce a large amount of Al into the glass. 2 O 3 (≥16wt%), thereby improving the chemical stability of the glass, and increasing the hardness, impact strength and elastic modulus of the glass. When high-aluminum glass is melted, the viscosity of the glass liquid is high, bubbles are not easy to discharge, and it is difficult to clarify. Therefore, in order to reduce the difficulty of clarifying the glass, As is added during the glass melting process. 2 O 3 , Sb 2 O 3 and PbO and other clarifiers. At the same time, these raw materials are generally used with nitrates to improve the clarification effect, but As 2 O 3 , Sb 2 O 3 In the process of glass melting, raw materials such as arsenic, antimony, and lead will be produced, which is easy to cause pollution in the preparation process. At the same time, nitrates will also form nitrogen oxides (NO X ), causing pollution to the environment.
[0004] In order to improve the living environment, improve the quality of life, and cherish health, elements that are harmful to the human body and the environment (such as Pb, Cd, Cr, Sb, As, etc.) should be avoided as much as possible. In addition, the glass cover will come into contact with the human body in large quantities during use. The glass cover will carry a large number of bacteria during long-term use. Many metal ions have antibacterial effects, among which silver ions have the best sterilization effect, with broad-spectrum antibacterial properties and safety, and the required concentration is extremely low, and the general dosage is "10 -6 "Mass fraction can kill bacteria, however, the inventors' research shows that when silver salt is added during the preparation of the glass system of the present invention, Ag can precipitate (Ag + dissolution), which not only affects the antibacterial effect, but also affects the light transmittance and mechanical properties. Summary of the invention
[0005] The present invention provides a high-strength, environmentally friendly, antibacterial cover glass, and a preparation method and application thereof. The cover glass provided by the present invention has good performance, not only in terms of strength, transmittance and environmental protection. The silver ions introduced into the cover glass can play an antibacterial role. At the same time, the glass can produce a black stray light-eliminating layer under a reducing atmosphere. It also has good chemical stability and good processing performance, and can be applied to various high-transmittance, high-precision cover glasses.
[0006] In order to achieve the above object, the technical solution of the present invention is:
[0007] In a first aspect, a high-strength, environmentally friendly, antibacterial cover glass is provided, wherein the raw materials are calculated based on the mass fraction of oxides and are composed of the following components:
[0008] SiO 2 55.0~65.0%,Al 2 O 3 17.0~23.0%, B 2 O 3 2.0~4.0%, K 2 O 0~2.0%, Na 2 O9.0~15.0%, CaO 0~1.0%, MgO 0.5~3.0%, CeO 2 0.1~2.0%,Bi 2 O 3 0~3%, Ag 2 O0.1~3%,In 2 O 3 0~3.0%;Bi 2 O 3 WithIn 2 O 3 If the content is different, it is 0.
[0009] The sum of the mass fractions of each component is 100%.
[0010] The present invention introduces Ag into the above glass system. 2 O, giving the glass a certain antibacterial ability, while Al 2 O 3 and Ag 2 O improves the strength of the glass; in addition, the present invention improves the strength of the glass by B 2 O 3 、CeO 2 、Bi 2 O 3 、In 2 O 3 And their synergy can reduce the precipitation of Ag, thereby ensuring that the cover glass has high strength, high transmittance and antibacterial properties.
[0011] In addition, Ag + It is an essential antibacterial ingredient. The present invention has found that Ag 2 When the O content exceeds 3%, the antibacterial performance of the glass will decrease, the cost of the glass will increase, and the precipitation of Ag will increase, affecting the light transmittance of the glass. 2 When the O content is less than 0.1%, the antibacterial property of the glass is poor.
[0012] The glass system provided by the present invention contains SiO 2 、Al 2 O 3 , B 2 O 3 , K 2 O、Na 2 O, CaO, MgO, CeO 2 、Bi 2 O 3 、Ag 2 O、In 2 O 3 , by precisely controlling the SiO 2 、Al 2 O 3 , B 2 O 3 , K 2 O、Na 2 O, CaO, MgO, CeO 2 、Bi 2 O 3 、Ag 2 O and In 2 O 3 These ingredients and their contents achieve excellent comprehensive properties, including strength, chemical stability, optical transmittance, Ag + Dissolution amount, etc. SiO 2 , CaO, B 2 O 3 The integrated effect of SiO and MgO improves the thermal and chemical stability of glass. 2 As the main components, they provide the basis of the structure; CaO, B 2 O 3 The synergistic effect of Al and CaO regulates the thermal expansion coefficient and enhances the chemical stability. The addition of MgO further improves the corrosion resistance of glass in complex environments and prolongs its service life. 2 O 3 ,MgO,B 2 O 3 and CeO 2 The introduction of Al improves the optical quality and enhances the optical transmittance of glass materials.2 O 3 , MgO and CaO content, effectively reducing the tendency of glass crystallization, and further improving the permeability of the formed glass. 2 O、CeO 2 and B 2 O 3 The combined effect of the above reduces the difficulty of glass clarification and reduces defects such as bubbles in the glass melting process. 2 O 3 As a flux, it accelerates the dissolution and clarification of glass and reduces the difficulty of glass molding.
[0013] In a second aspect, a method for preparing the above-mentioned high-strength, environmentally friendly, antibacterial cover glass is provided, wherein the raw materials are uniformly mixed in proportion to obtain a mixture, and the mixture is sequentially melted, stirred, clarified, and formed.
[0014] In a third aspect, a use of the above-mentioned high-strength, environmentally friendly, antibacterial cover glass in the cover of an electronic product display screen.
[0015] The beneficial effects of the present invention are:
[0016] 1. The high-strength environmentally friendly antibacterial cover glass provided by the present invention has a bending strength greater than 129MPa, a maximum optical transmittance of a 2mm glass sample greater than 91.3%, and Ag + The dissolution amount is greater than 56.7%.
[0017] 2. The high-strength, environmentally friendly, antibacterial cover glass provided by the present invention has a level 1 acid resistance and moisture resistance, good mechanical properties and processing properties, and can be used as the main material for various digital product covers. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0019] Figure 1 It is a comparative curve chart of the transmittance of 2 mm thick glass products of comparative example 1 and example 2 in the wavelength range of 350 to 1000 nm.
[0020] Figure 2 It is a comparison chart of haze and bending strength of glass materials of Examples 1 to 9 and Comparative Examples 1 to 6. DETAILED DESCRIPTION
[0021] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0022] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0023] In view of the fact that the existing cover glass cannot take into account strength, transmittance and antibacterial performance at the same time, the present invention proposes a high-strength environmentally friendly antibacterial cover glass and a preparation method and application thereof.
[0024] A typical embodiment of the present invention provides a high-strength environmentally friendly antibacterial cover glass, wherein the raw materials are composed of the following components according to the mass fraction of oxides:
[0025] SiO 2 55.0~65.0%,Al 2 O 3 17.0~23.0%, B 2 O 3 2.0~4.0%, K 2 O 0~2.0%, Na 2 O9.0~15.0%, CaO 0~1.0%, MgO 0.5~3.0%, CeO 2 0.1~2.0%,Bi 2 O 3 0~3.0%, Ag 2 O0.1~3.0%,In 2 O 3 0~3.0%;Bi 2 O 3 WithIn 2 O 3 If the content is different, it is 0.
[0026] In the present invention, SiO 2 It is a glass-forming oxide. As the main component of glass, it provides the basic framework of the structure and gives the glass good chemical stability and mechanical strength. 2 The content can reduce the thermal expansion coefficient of glass and improve the thermal stability, chemical stability, softening temperature, heat resistance, hardness and mechanical strength of glass. 2Too high a content of SiO may result in an increase in melting point and difficulty in processing; 2 Too low a content of SiO may weaken chemical stability and mechanical strength. 2 The content of can be 55.5-65.0%, 55.5-62.0%, 55.5-60.0%, 55.5-57.0%, 55.0-62.0%, 56.0-60.0%, 56.0-57.0%, 57.0-62.0%, etc.
[0027] Al 2 O 3 It is an essential component to improve the chemical stability of glass, which can reduce the tendency of glass crystallization. It is also a component to increase the hardness and mechanical strength of glass and increase the tensile elastic modulus. In the glass network structure, alumina is a network intermediate oxide, between the network generator and the network exogenous body. In glass with an alumina content of less than 2%, alumina basically exists in a four-coordinated form. In medium / high alumina silicate glass, aluminum exists in two coordination forms, one of which is four-coordinated. In this case, A1 3+ Located in the tetrahedron to form aluminum oxide tetrahedron [AlO 4 ]; one is six-coordinated, namely A1 3+ Located in the octahedron to form an aluminum oxide octahedron [AlO 6 ]. When it is in a high coordination state, the glass has a higher refractive index and a smaller molecular volume; when it is in a low coordination state, the refractive index and density of the glass are reduced. Al 2 O 3 The content of can be 17.0-22.0%, 17.0-21.0%, 17.0-20.0%, 17.0-19.5%, 17.0-19.0%, 17.0-18.0%, 17.0-18.5%, 17.5-23.0%, 17.5-22.0%, 17.5-21.0%, 17.5-20.0%, 17.5-19.5%, 17.5-19.0%, 18.0-23.0%, 18.0-22. 0%, 18.0~21.0%, 18.0~20.0%, 18.0~19.5%, 18.0~19.0%, 18.0~18.5%, 18.5~23.0%, 18.5~22.0%, 18.5~21.0%, 18.5~20.0%, 18.5~19.5%, 18.5~19.0%, 19.0~23.0%, 19.0~22.0%, 19.0~21.0%, 19.0~20.0%, etc.
[0028] In the embodiment of the present invention, in terms of mass percentage, B 2 O 3 The content of B is 2.0-4.0%.2 O 3 It is also a glass-forming oxide, which is a triangular boron oxide [BO 3 ] and the boron-oxygen tetrahedron [BO 4 ] is a structural unit, which forms a structural network with silicate tetrahedron in borosilicate glass. 2 O 3 At high temperatures, it can reduce the viscosity of the glass, and at low temperatures, it can increase the viscosity of the glass, so B 2 O 3 Glass with a higher content has a wider forming temperature range. 2 O 3 It also plays a role in fluxing, accelerating the dissolution and clarification of glass. 2 O 3 When the amount added is too high, the expansion coefficient of the glass will increase due to the increase of boron-oxygen triangles, resulting in boron anomaly and reducing the chemical stability of the glass. 2 O 3 As a flux, it can make Ag + Stable, when B 2 O 3 When the content exceeds 60wt%, Ag + The dissolution amount is too high and cannot stabilize Ag. + The effect of 2 O 3 The content of can be 2.0-3.8%, 2.0-3.5%, 2.0-3.3%, 2.0-3.0%, 2.0-2.5%, 2.2-4.0%, 2.2-3.8%, 2.2-3.5%, 2.2-3.3%, 2.2-3.0%, 2.2-2.5%, 2.5-4.0%, 2.5-3.8%, 2.5-3.5%, 2.5-3.3%, 2.5-3.0%, 3.0-4.0%, 3.0-3.8%, 3.0-3.5%, 3.0-3.3% and the like.
[0029] In the present invention, K 2 O and Na 2 O is the oxide of the glass network. Alkali metal ions are easy to move and diffuse in the glass, which can reduce the viscosity of the glass at high temperature and make the glass easy to melt. It is a good flux, but the amount of introduction should not be too much. Too much introduction will increase the thermal expansion coefficient of the glass and reduce the chemical stability, thermal stability and mechanical strength of the glass. In addition, Na in glass + It is a necessary condition for achieving chemical strengthening. 2The content of O can be 0.1-2.0%, 0.5-2.0%, 0.8-2.0%, 0.8-1.8%, 0.8-1.5%, 0.8-1.3%, 1.0-2.0%, 1.0-1.5%, 1.0-1.3%, 1.3-2.0%, 1.3-1.8%, 1.3-1.5%, 1.5-2.0%, 1.8-2.0%, etc. 2 The content of O can be 9.0-15.0%, 9.0-14.5%, 9.0-14.0%, 9.0-13.0%, 9.0-12.0%, 9.0-11.0%, 9.0-10.0%, 10.0-15.0%, 10.0-14.5%, 10.0-14.0%, 10.0-13.0%, 10.0-12.0%, 10.0-1 1.0%, 11.0~15.0%, 11.0~14.5%, 11.0~14.0%, 11.0~13.0%, 11.0~12.0%, 12.0~15.0%, 12.0~14.5%, 12.0~14.0%, 12.0~13.0%, 13.0~15.0%, 13.0~14.5%, 13.0~14.0%, etc.
[0030] In the present invention, the introduction of CaO can increase the chemical stability and mechanical strength of the glass, but when the amount introduced is large, the glass is easy to crystallize and the thermal stability of the glass is reduced. At the same time, CaO can reduce the viscosity of the glass at high temperature, which is conducive to clarification; the introduction of MgO can improve the thermal stability of the glass, and the introduction of MgO will reduce the thermal expansion coefficient of the glass, but too much MgO will increase the viscosity of the glass, making it difficult to clarify the glass. MgO and CaO together enhance the mechanical strength and chemical durability of the glass in the present invention, and the addition of MgO is particularly helpful to reduce the increase in the thermal expansion coefficient caused by CaO. The content of CaO can be 0.1-1.0%, 0.1-0.8%, 0.1-0.5%, 0.4-1.0%, 0.4-0.8%, 0.4-0.6%, 0.4-0.5%, 0.5-1.0%, 0.5-0.8%, 0.6-1.0%, 0.6-0.8%, etc. The content of MgO can be 0.5-2.5%, 0.5-2.0%, 0.5-1.5%, 0.5-1.0%, 1.0-3.0%, 1.0-2.5%, 1.0-2.0%, 1.0-1.5%, 1.5-3.0%, 1.5-2.5%, 1.5-2.0%, 2.0-3.0%, 2.0-2.5%, 2.5-3.0%, etc.
[0031] In the present invention, CeO 2 CeO is a variable valence oxide. 2High temperature decomposes oxygen. For every 1°C increase in temperature, more oxygen can be separated from its chemical bonds, and the clarification effect is greater. The solubility of oxygen decreases with increasing temperature, thus producing a clarification effect. At the same time, CeO 2 With excellent thermal stability and physical properties, it can improve the impact resistance and heat resistance of glass, making the glass harder and more durable. 2 As a strong oxidant, it can keep silver in the glass in the form of ions at high temperatures, preventing the precipitation of silver colloid or silver particles. 2 The content of can be 0.1-1.5%, 0.1-1.0%, 0.1-0.8%, 0.1-0.5%, 0.1-0.3%, 0.3-2.0%, 0.3-1.5%, 0.3-1.0%, 0.3-0.8%, 0.3-0.5%, 0.5-2.0%, 0.5-1.5%, 0.5-1.0%, 0.5-0.8%, 0.8-2.0%, 0.8-1.5%, 0.8-1.0%, 1.0-2.0%, 1.0-1.5%, 1.5-2.0%, etc.
[0032] In the present invention, by Bi 2 O 3 、In 2 O 3 Or the synergistic effect of the two can increase the Ag content in glass + stability and reduce the amount of Ag precipitation. 2 O 3 The addition of Bi can improve the refractive index and dispersion ability. 2 O 3 It also helps improve the thermal stability of glass and enhances its light absorption capacity. 2 O 3 The introduction of Bi needs to be precisely controlled. 2 O 3 This may lead to a significant decrease in the chemical stability of the glass, especially when reacting with reducing gases. 2 O 3 In the glass melting process, it may cause serious corrosion to the melting container, which limits its application in glass production. In addition, too much Bi 2 O 3 It may also promote the crystallization of glass, affecting its transparency and optical uniformity. 2 O 3 If the content is insufficient, it is difficult to improve the optical properties. 2 The introduction of O can improve the optical properties of glass. 2O has good absorption and reflection properties, so it can effectively block the penetration of ultraviolet and visible light, and improve the light transmittance and light-shielding properties of the glass. Secondly, it can improve the chemical stability and mechanical strength of the glass. 2 O can form a composite glass structure and a crystal hardened layer with other glass additives to improve the corrosion resistance, hardness and toughness of the glass material, thereby enhancing its mechanical strength and impact resistance. + It is an essential antibacterial ingredient. The present invention has found that Ag 2 When the O content exceeds 3%, the antibacterial performance of the glass will decrease, the cost of the glass will increase, and the precipitation of Ag will increase, affecting the light transmittance of the glass. 2 When the O content is less than 0.1%, the antibacterial property of the glass is poor. 2 O 3 It can improve the thermal conductivity and mechanical properties of glass materials. When the indium content is low, it can effectively improve the thermal stability and heat resistance of the glass; when the indium content increases, the density and refractive index of the glass will also increase. 2 O 3 Too much content can also easily cause serious discoloration of the glass. 2 O 3 The content of Ag can be 0-2.5%, 0-1.0%, 0.1-3.0%, 0.1-2.5%, 0.1-2.0%, 0.1-1.5%, 0.1-1.0%, 0.1-0.8%, 0.1-0.5%, 0.5-1.5%, 0.5-1.0%, 0.5-0.8%, 0.8-1.0%, etc. 2 The content of O can be 0.1-3.0%, 0.1-2.5%, 0.1-2.0%, 0.1-1.5%, 0.1-1.0%, 0.1-0.5%, 0.1-0.3%, 0.1-0.2%, 0.2-0.3%, 0.3-0.5%, 0.3-1.0%, etc. 2 O 3 The content of can be 0-1.0%, 0.1-3.0%, 0.1-2.5%, 0.1-2.0%, 0.1-1.5%, 0.1-1.0%, 0.1-0.9%, 0.1-0.8%, 0.1-0.7%, 0.1-0.6%, 0.1-0.5%, 0.1-0.4%, 0.1-0.3%, 0.3-1.0%, 0.3-0.8%, 0.3-0.7%, 0.3-0.6%, 0.3-0.5%, 0.3-0.4%, 0.6-0.8%, etc.
[0033] In some embodiments, Na 2 The content of O is more than two-ninths of that of K 2O content. Studies have shown that glass with this component condition has better effect.
[0034] In some embodiments, B 2 O 3 The content is less than four-seventeenth times of Al 2 O 3 Research shows that glass with this component has better effect.
[0035] Another embodiment of the present invention provides a method for preparing the above-mentioned high-strength, environmentally friendly, antibacterial cover glass, which comprises uniformly mixing the raw materials in proportion to obtain a mixture, and sequentially melting, stirring, clarifying, and molding the mixture.
[0036] In some embodiments, the melting temperature is 1500-1580° C. Specifically, the melting time is 8-30 hours, which is helpful for clarifying the glass liquid.
[0037] In some embodiments, the stirring speed is 10 to 20 r / min, and the stirring time is 3 to 12 hours. There are certain requirements for the uniformity of the liquid before glass forming, so it is necessary to stir the glass liquid at a certain speed for a period of time before forming to improve the uniformity of the liquid. When the uniformity of the liquid is low, the liquid is prone to stratification or agglomeration, making it difficult to melt and homogenize the glass, and even causing streaks or stone defects in severe cases.
[0038] In some embodiments, the molding temperature is 1350-1400° C., and the molding time is 5-25 minutes. Rapid molding of glass can prevent the generation of secondary bubbles and impurities.
[0039] In some embodiments, annealing is performed after forming to eliminate the internal stress of the glass and meet the requirements of subsequent cold processing. Specifically, the annealing temperature is 500-550°C.
[0040] A third embodiment of the present invention provides an application of the above-mentioned high-strength, environmentally friendly, antibacterial cover glass in a cover of an electronic product display screen.
[0041] In some embodiments, the electronic product is a mobile phone, a camera, or a computer.
[0042] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.
[0043] The performance parameters in the following embodiments are measured according to the following methods:
[0044] The thermal expansion coefficient α of the glass sample was tested using the DIL 402 expansion coefficient tester produced by NETZSCH, Germany. Sample preparation: The glass sample was polished into a cylindrical glass strip of Φ6×50mm, and the two end surfaces were parallel. The heating rate was set to 5℃ / min, and the data acquisition cycle was 20ms. Refer to GB / T7962.16~2010.
[0045] The softening point temperature of the glass sample is tested using the Model PPV-1000 / 1200 plate viscometer produced by Orton. Sample preparation: The glass sample is polished into a cylindrical glass strip of Φ6×6mm, and the two end faces are parallel. The sample is placed between the top and bottom discs, which are made of heat-resistant metal alloys with a diameter of 44mm and a thickness of 6mm. The top metal disc is connected to the bottom of the probe rod. Two very thin platinum films (40mm in diameter and 0.001 inches thick) are placed between the sample and the top and bottom discs to facilitate sampling and sample placement. Refer to ASTM C-1351M.
[0046] The transmittance test was carried out using a UV-visible-infrared spectrophotometer.
[0047] After the surface of the polished glass sample is corroded by the test medium with acidity of pH2.9, pH4.6, and pH6.0, observe the time when the purple-blue interference color appears on the glass surface, or the surface becomes mottled or falls off under an incandescent lamp. The acid resistance stability of colorless optical glass is classified in descending order according to the length of time. Refer to GB / T 7962.14~2010.
[0048] Polished glass samples are kept at a constant temperature and humidity of 50°C and 85% relative humidity for 20 hours, and the moisture resistance stability of colorless optical glass is classified in descending order by comparing the turbidity values with those of standard samples H (BaK7) and H (ZK9). Refer to GB / T7962.15~2010.
[0049] The haze of glass samples was tested using the Qunlong CS series haze tester. Sample preparation: The glass samples were ground and polished into Φ32×20mm circular glass sheets. The spectral response was the CIE spectral function Y / V(λ), with a wavelength range of 400-700nm, a wavelength interval of 10nm, and a resolution of 0.01 units. Refer to GB / T24010.
[0050] XPS spectrum analysis of Ag in glass using AXIS SUPRA photoelectron spectrometer + Dissolution amount, energy scanning range 1-1400eV, sample size less than 25mm×25mm×10mm, qualitative analysis of element type, content and valence state of glass samples. The vacuum degree of the analysis chamber is less than 5.0×10 -9Torr, X-ray source: Al Ka (1486.6 eV), scanning mode: Spectroscope, element scanning range: Li in the periodic table 3 -U 92 All elements between. Refer to GB / T 30704-2014.
[0051] The bending strength of glass samples is tested using the three-point bending method. The glass sample is processed into the required size for the test, and then the glass sample is placed between two supporting points and a fixed load is applied perpendicular to the center of the sample. Then, by applying different bending moments, the bending stress and strain of the glass are measured under different conditions. Finally, the bending strength of the glass is determined. Refer to GB / T 37781-2019.
[0052] Example 1
[0053] The components of the high-strength environmentally friendly antibacterial cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .
[0054] The preparation method of high-strength, high-transmittance, environmentally friendly and antibacterial cover glass is as follows: quartz sand, aluminum hydroxide, boric acid, potassium carbonate, sodium carbonate, calcium carbonate, basic magnesium carbonate, cerium dioxide, bismuth oxide, silver phosphate, and indium oxide are used as raw materials, and after being fully mixed, they are melted at 1500°C for 8 hours, mechanically stirred (10r / min, 3 hours), assisted by high-temperature clarification, and leak-molded at 1350°C (molding time is 5 minutes) to obtain glass blanks. The glass blanks are placed in an annealing furnace heated to 520°C in advance for annealing to eliminate the stress in the glass to meet the requirements of later cold processing.
[0055] Example 2
[0056] The components of the high-strength environmentally friendly antibacterial cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figures 1-2 .
[0057] In the preparation method of high-strength, environmentally friendly, antibacterial cover glass, the melting temperature is 1550°C, the melting time is 16 hours, mechanical stirring (20r / min, 12h), the molding temperature is 1400°C, the molding time is 15min, and the other preparation steps and parameters are the same as those in Example 1.
[0058] Example 3
[0059] The components of the high-strength environmentally friendly antibacterial cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .
[0060] In the preparation method of high-strength, environmentally friendly, antibacterial cover glass in this embodiment, the melting temperature is 1580°C and the melting time is 30h; mechanical stirring (20r / min, 12h), the molding temperature is 1400°C, and the molding time is 25min. The other preparation steps and parameters are the same as those in Example 1.
[0061] Example 4
[0062] The components of the high-strength environmentally friendly antibacterial cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .
[0063] In the preparation method of high-strength, environmentally friendly, antibacterial cover glass in this embodiment, the melting temperature is 1560°C and the melting time is 20h; mechanical stirring (20r / min, 14h), the molding temperature is 1400°C, and the molding time is 25min. The other preparation steps and parameters are the same as those in Example 1.
[0064] Example 5
[0065] The components of the high-strength environmentally friendly antibacterial cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .
[0066] In the preparation method of high-strength, environmentally friendly, antibacterial cover glass in this embodiment, the melting temperature is 1520°C and the melting time is 25h; mechanical stirring (20r / min, 14h), the molding temperature is 1380°C, and the molding time is 25min. The other preparation steps and parameters are the same as those in Example 1.
[0067] Example 6
[0068] The components of the high-strength environmentally friendly antibacterial cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .
[0069] In the preparation method of high-strength, environmentally friendly, antibacterial cover glass in this embodiment, the melting temperature is 1560°C and the melting time is 30h; mechanical stirring (20r / min, 12h), the molding temperature is 1400°C, and the molding time is 25min. The other preparation steps and parameters are the same as those in Example 1.
[0070] Example 7
[0071] The components of the high-strength environmentally friendly antibacterial cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .
[0072] In the preparation method of high-strength, environmentally friendly, antibacterial cover glass in this embodiment, the melting temperature is 1550°C and the melting time is 30h; mechanical stirring (20r / min, 14h), the molding temperature is 1400°C, and the molding time is 25min. The other preparation steps and parameters are the same as those in Example 1.
[0073] Example 8
[0074] The components of the high-strength environmentally friendly antibacterial cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .
[0075] In the preparation method of high-strength, environmentally friendly, antibacterial cover glass in this embodiment, the melting temperature is 1550°C and the melting time is 30h; mechanical stirring (20r / min, 14h), the molding temperature is 1400°C, and the molding time is 20min. The other preparation steps and parameters are the same as those in Example 1.
[0076] Example 9
[0077] The components of the high-strength environmentally friendly antibacterial cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .
[0078] In the preparation method of high-strength, environmentally friendly, antibacterial cover glass in this embodiment, the melting temperature is 1560°C and the melting time is 30h; mechanical stirring (20r / min, 14h), the molding temperature is 1400°C, and the molding time is 20min. The other preparation steps and parameters are the same as those in Example 1.
[0079] Comparative Examples 1 to 6
[0080] The components of the glasses of Comparative Examples 1 to 6, the weight percentage of each component, and the physical properties of the glasses obtained are shown in Tables 2, 4, Figures 1-2 .
[0081] The preparation steps and parameters of the glass in Comparative Examples 1 to 6 are the same as those in Example 2.
[0082] Table 1 Components and contents of the environmentally friendly cover glass of Examples 1 to 9 of the present invention
[0083]
[0084]
[0085] Table 2 Components and contents of environmentally friendly cover glass of comparative examples 1 to 6 of the present invention
[0086]
[0087] Table 3 Performance test results of glass samples of Examples 1 to 9
[0088]
[0089] Table 4 Performance test results of glass samples of Comparative Examples 1 to 6
[0090]
[0091]
[0092] Examples 1 to 9 By rationally adding the corresponding components and controlling the ratio of the components in the raw materials, the optical transmittance, haze performance, bending strength and Ag content of the glass are improved. + Better ion dissolution performance. As can be seen from Table 3, the optical transmittance of the high-strength environmentally friendly antibacterial cover glass prepared in Examples 1 to 9 of the present invention is as follows: within the wavelength range of 350 to 1000 nm, the maximum transmittance is ≥ 92.1%. The comprehensive performance is better than the glass involved in Comparative Examples 1 to 6, and it has good acid / moisture resistance stability, and can maintain the stability of the internal structure of the glass for a long time.
[0093] As can be seen from the above, the high-strength environmentally friendly antibacterial cover glass provided in Examples 1 to 9 of the present invention has excellent optical transmittance, low haze, high bending strength and Ag + Ion dissolution and good processing performance. This is because in Examples 1 to 9 of the present invention, the proportion of each component raw material is adjusted in the preparation of the high-strength environmentally friendly antibacterial cover glass, and a suitable stirring speed and time are set. Therefore, the high-strength environmentally friendly antibacterial cover glass of the present invention has a high optical transmittance, a low haze, a high bending strength and Ag + Ion dissolution capacity, has broad application prospects.
[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high-strength environmentally friendly antibacterial cover glass, characterized in that: The raw materials are composed of the following components according to the mass fraction of oxides: SiO2 55.0~65.0%, Al2O3 17.0~23.0%, B2O3 2.0~4.0%, K2O 0~2.0%, Na2O9.0~15.0%, CaO 0~1.0%, MgO 0.5~3.0%, CeO2 0.1~2.0%, Bi2O3 0~3%, Ag2O0.1~3%, In2O3 0~3.0%; if the content of Bi2O3 and In2O3 is different, the value is 0.
2. The high-strength environmentally friendly antibacterial cover glass according to claim 1, characterized in that: The content of SiO2 is 55.5-65.0%, or 55.5-62.0%, or 55.5-60.0%, or 55.5-57.0%, or 55.0-62.0%, or 56.0-60.0%, or 56.0-57.0%, or 57.0-62.0%; Or, the content of Al2O3 is 17.0-22.0%, or 17.0-21.0%, or 17.0-20.0%, or 17.0-19.5%, or 17.0-19.0%, or 17.0-18.0%, or 17.0-18.5%, or 17.5-23.0%, or 17.5-22.0%, or 17.5-21.0%, or 17.5-20.0%, or 17.5-19.5%, or 17.5-19.0%, or 18.0-23.0%, or 18.0-2 2.0%, or 18.0-21.0%, or 18.0-20.0%, or 18.0-19.5%, or 18.0-19.0%, or 18.0-18.5%, or 18.5-23.0%, or 18.5-22.0%, or 18.5-21.0%, or 18.5-20.0%, or 18.5-19.5%, or 18.5-19.0%, or 19.0-23.0%, or 19.0-22.0%, or 19.0-21.0%, or 19.0-20.0%; Or, the content of B2O3 is 2.0-3.8%, or 2.0-3.5%, or 2.0-3.3%, or 2.0-3.0%, or 2.0-2.5%, or 2.2-4.0%, or 2.2-3.8%, or 2.2-3.5%, or 2.2-3.3%, or 2.2-3.0%, or 2.2-2.5%, or 2.5-4.0%, or 2.5-3.8%, or 2.5-3.5%, or 2.5-3.3%, or 2.5-3.0%, or 3.0-4.0%, or 3.0-3.8%, or 3.0-3.5%, or 3.0-3.3%; Or, the content of K2O is 0.1-2.0%, or 0.5-2.0%, or 0.8-2.0%, or 0.8-1.8%, or 0.8-1.5%, or 0.8-1.3%, or 1.0-2.0%, or 1.0-1.5%, or 1.0-1.3%, or 1.3-2.0%, or 1.3-1.8%, or 1.3-1.5%, or 1.5-2.0%, or 1.8-2.0%; The content of Na2O is 9.0-15.0%, or 9.0-14.5%, or 9.0-14.0%, or 9.0-13.0%, or 9.0-12.0%, or 9.0-11.0%, or 9.0-10.0%, or 10.0-15.0%, or 10.0-14.5%, or 10.0-14.0%, or 10.0-13.0%, or 10.0-12.0%, or 10.0- 11.0%, or 11.0-15.0%, or 11.0-14.5%, or 11.0-14.0%, or 11.0-13.0%, or 11.0-12.0%, or 12.0-15.0%, or 12.0-14.5%, or 12.0-14.0%, or 12.0-13.0%, or 13.0-15.0%, or 13.0-14.5%, or 13.0-14.0%; Or, the CaO content is 0.1-1.0%, or 0.1-0.8%, or 0.1-0.5%, or 0.4-1.0%, or 0.4-0.8%, or 0.4-0.6%, or 0.4-0.5%, or 0.5-1.0%, or 0.5-0.8%, or 0.6-1.0%, or 0.6-0.8%; Or, the content of MgO is 0.5-2.5%, or 0.5-2.0%, or 0.5-1.5%, or 0.5-1.0%, or 1.0-3.0%, or 1.0-2.5%, or 1.0-2.0%, or 1.0-1.5%, or 1.5-3.0%, or 1.5-2.5%, or 1.5-2.0%, or 2.0-3.0%, or 2.0-2.5%, or 2.5-3.0%; Or, the content of CeO2 is 0.1-1.5%, or 0.1-1.0%, or 0.1-0.8%, or 0.1-0.5%, or 0.1-0.3%, or 0.3-2.0%, or 0.3-1.5%, or 0.3-1.0%, or 0.3-0.8%, or 0.3-0.5%, or 0.5-2.0%, or 0.5-1.5%, or 0.5-1.0%, or 0.5-0.8%, or 0.8-2.0%, or 0.8-1.5%, or 0.8-1.0%, or 1.0-2.0%, or 1.0-1.5%, or 1.5-2.0%; Or, the content of Bi2O3 is 0-2.5%, or 0-1.0%, or 0.1-3.0%, or 0.1-2.5%, or 0.1-2.0%, or 0.1-1.5%, or 0.1-1.0%, or 0.1-0.8%, or 0.1-0.5%, or 0.5-1.5%, or 0.5-1.0%, or 0.5-0.8%, or 0.8-1.0%; Or, the content of Ag2O is 0.1-3.0%, or 0.1-2.5%, or 0.1-2.0%, or 0.1-1.5%, or 0.1-1.0%, or 0.1-0.5%, or 0.1-0.3%, or 0.1-0.2%, or 0.2-0.3%, or 0.3-0.5%, or 0.3-1.0%; Or, the content of In2O3 is 0-1.0%, or 0.1-3.0%, or 0.1-2.5%, or 0.1-2.0%, or 0.1-1.5%, or 0.1-1.0%, or 0.1-0.9%, or 0.1-0.8%, or 0.1-0.7%, or 0.1-0.6%, or 0.1-0.5%, or 0.1-0.4%, or 0.1-0.3%, or 0.3-1.0%, or 0.3-0.8%, or 0.3-0.7%, or 0.3-0.6%, or 0.3-0.5%, or 0.3-0.4%, or 0.6-0.8%.
3. The high-strength environmentally friendly antibacterial cover glass according to claim 1, characterized in that Na The content of 2O is greater than two-ninths of the content of K2O; Or, the content of B2O3 is less than four seventeenths of the content of Al2O3.
4. A method for preparing the high-strength environmentally friendly antibacterial cover glass according to claim 1, characterized in that: The raw materials are mixed uniformly according to a proportion to obtain a mixture, and the mixture is melted, stirred, clarified and formed in sequence to obtain the product.
5. The method for preparing the high-strength environmentally friendly antibacterial cover glass according to claim 4, characterized in that: The melting temperature is 1500-1580° C.; preferably, the melting time is 8-30 hours.
6. The method for preparing the high-strength environmentally friendly antibacterial cover glass according to claim 4, characterized in that: The stirring speed is 10-20 r / min, and the stirring time is 3-12 h.
7. The method for preparing the high-strength environmentally friendly antibacterial cover glass according to claim 4, characterized in that: The molding temperature is 1350-1400°C, and the molding time is 5-25 minutes.
8. The method for preparing the high-strength environmentally friendly antibacterial cover glass according to claim 4, characterized in that: Annealing is performed after forming; preferably, the annealing temperature is 500-550°C.
9. Use of the high-strength, environmentally friendly, antibacterial cover glass according to any one of claims 1 to 3 in the cover of an electronic product display screen.
10. The use according to claim 9, characterized in that: The electronic product is a mobile phone, a camera or a computer.